P-161 Improving the content and timeliness of discharge letters from a hospice inpatient unit. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Rimmer, Joanne; Hodgson, Aruna
Abstract : Background: When a patient is discharged from an inpatient setting back into the community, essential information about their condition and its treatment must be communicated accurately and efficiently via a comprehensive discharge letter to the relevant health care professionals. Aims: To audit the content and timeliness of discharge letters from a hospice inpatient unit and rectify deficiencies identified by agreeing and implementing effective interventions. To re-audit the impact of changes made, thereby completing the audit cycle. Methods: An initial audit identified that the standards for hospice discharge letters were not being met in several areas. Following this, four main strategies were implemented to achieve improvements: 1. Introduction of a discharge letter proforma 2. Enhanced communication systems between the medical team and clinical secretaries 3. Discharge letters faxed, rather than posted to ensure timeliness of delivery 4. Ongoing monitoring of when letters were being sent, with quarterly reports presented to the medical team. One year following introduction of these changes, a retrospective re-audit was undertaken of twenty-five consecutive patients discharged from a hospice inpatient unit. Results: All areas of deficiencies previously identified were improved upon in the re-audit. The discharge letter proforma succeeded in standardising the format and content of letters, ensuring key positive and negative information was recorded. The systems put in place to ensure timeliness of letter-sending resulted in 96% being sent out within one working day, (versus 45% previously). These improvements have enhanced communication between the hospice, hospital and community. Conclusions: Further alterations to hospice discharge letters and ongoing monitoring are required to maintain and optimise standards. The audit work undertaken has demonstrated that effective clinical changes can be achieved through collaboration with colleagues to agree achievable action plans, and by ongoing good team working to attain high standards and additonal improvements in practice.